Ombudsman and public accountability of bureaucracy: A case for Bangladesh ombudsman - Abedin, Najmul (2000)
Pursuing development through interventionist mode of governance has led to explosion of modern government's functions followed inevitably by a rapid and bewildering growth of bureaucratic power, rendering its control and public accountability totally ineffective. The system of ombudsman has been devised as one of the effective tools to manage public complaints against bureaucratic excesses and encroachments. The author takes a look at relevant issues and arguments in favour of ombudsman in different countries, in general, and Bangladesh, in particular. - Reproduced
Keywords: Bureaucracy - Bangladesh; Accountability - Bangladesh; Ombudsman - Bangladesh; Ombudsman